Best practices in sustainable building design - Vassigh, Shahin; Ozer, Ebru ;Spiegelhalter, Thomas (Florida, United States : J. Ross Publishing, 2013)
This text and DVD is an interactive learning environment composed of seven content areas: building form, envelopes, structures, climate control systems, renewable energy, lighting, and landscape design.
1. Building Form -- 2. Building Envelopes -- 3. Structure -- 4. Climate Control -- 5. Renewable Energy -- 6. Lighting -- 7. Landscape -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: SUSTAINABLE BUILDINGS -- DESIGN AND CONSTRUCTION